Astilbe chinensis Modulates Platelet Function via Impaired MAPK and PLCγ2 Expression. (5th August 2018) - Jeon, Bo-Ra; Irfan, Muhammad; Lee, Seung Eun; Lee, Jeong Hoon; Rhee, Man Hee
Abstract : Background . Platelets play major role in maintaining hemostasis while hyperactivation of platelets may lead to arterial thrombosis. Natural products and ethnomedicine have been shown to reduce the risk of cardiovascular diseases (CVDs). Astilbe chinensis is a perennial herb found in China, Korea, Russia, and Japan, which is also known for its medicinal effects, and has been used in Korean traditional medicine to treat inflammation, cancer, chronic bronchitis, and headache. We hypothesized that given herbal plant exhibits pharmacological activities against CVDs, and we specifically explored their effects on platelet function. Methodology . Platelet aggregation was evaluated using standard light-transmission aggregometry. Intracellular calcium mobilization was assessed using Fura-2/AM, and granule secretion (ATP release) was measured in a luminometer. Fibrinogen binding to integrin α I I b β 3 was assessed using flow cytometry. Phosphorylation of mitogen-activated protein kinase (MAPK) signaling molecules and activation of the phosphoinositide 3-kinase (PI3K)/Akt were assessed using western blots, and further, glycoprotein VI (GPVI) signaling components were studied using immunoprecipitation. Key Results . A. chinensis extracts potently and significantly inhibited platelet aggregation, calcium mobilization, granule secretion, and fibrinogen binding to integrin α I I b β 3 . Moreover, it significantly inhibited MAPK phosphorylation and expression of GPVI downstream signaling molecules. Conclusion . A. chinensis extract inhibited platelet aggregation and granule secretion and attenuated GPVI downstream signaling, indicating the potential therapeutic effects of this plant extract on the cardiovascular system and platelet function. We suggest that given plant extract may be a potent candidate to treat platelet-related CVDs and to be used as antiplatelet agent.